Technology Strategy Assessment of URC a roadmap to world class excellence - Sierra, Anthony B.
A technology strategy is a set of decisions related to the use and development of technology intended to confer advantage to the firm. It not properly formulated and planned will result to fewer breakthrough products, longer cycle times, lower success rates, and overall poorer new product performance. Technology strategy is vital for every company striving to achieve world class standard of quality performance excellence.